HERITABILITY AND PREVALENCE OF PERCEIVED PHYSICAL FATIGABILITY IN THE LONG LIFE FAMILY STUDY. (11th November 2018) - LaSorda, K R; Kuipers, A L; Boudreau, R M; Andersen, S L; Cosentino, S; Wojczynski, M K; Christensen, K; Glynn, N W
Abstract: Fatigability is an important early predictor in the disablement pathway, yet little is known about its genetic basis or association with age and sex. We examined prevalence and heritability of perceived physical fatigability using the Pittsburgh Fatigability Scale (PFS, 0–50, higher score=higher fatigability) in the Long Life Family Study. PFS scores (mean±SD) and proportion with higher fatigability (% PFS ≥15) increased across age strata: 60–69 (N=1009, 11.0 ± 7.6, 28%), 70–79 (N=847, 12.5 ± 8.1, 37%), 80–89 (N=253, 19.3 ± 9.9, 65.2%), and ≥90 (N=266, 28.6 ± 9.8, 89.5%), p<0.0001, adjusted for sex, field center, and family structure. Females reported higher perceived physical fatigability than males, with the largest difference in the 80–89 age strata, 74.8% vs. 53.5%, respectively, p<0.0001. After adjustment for age, sex, and field center, the residual heritability of fatigability was 0.263 (p=6.6x10^-9). Future research should target interventions aimed at those most at-risk for higher perceived physical fatigability early in the aging process.